3D PRINTING FOR DISSEMINATION OF MAYA ARCHITECTURAL HERITAGE: THE ACROPOLIS OF LA BLANCA (GUATEMALA) - R. Montuori; R. Montuori; L. Gilabert-Sansalvador; A. L. Rosado-Torres; A. L. Rosado-Torres (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2020)
This paper focuses on the use of 3D printing as a tool for the dissemination of Maya architectural heritage. The case study is the Acropolis of La Blanca, the main complex of this archaeological site located in the Peten department, Guatemala. One of the objectives of La Blanca Project was to create a model of the Acropolis as part of the strategy for dissemination and as a didactical resource for the Visitor Center. The documentation of this architectural complex with digital survey techniques allowed to obtain a high-fidelity model of the Acropolis’ buildings. In order to achieve this goal, it was necessary to develop a methodology for the reverse modelling of the Acropolis, starting from the data obtained by laser scanning. We developed a workflow to create a virtual replica of the Acropolis optimized for 3D printing. This model was first printed in 17 parts by using the FDM technology. Then, it was transported to Guatemala and, finally, it was reassembled and placed at the Visitor Center. Today, this physical replica of the Acropolis is an important resource that allows the visitors to have a complete view of the main complex of the site, which is not easy in the Guatemalan jungle. It also provides an exclusive view of some parts of the Acropolis, already studied by researchers and now protected with a soil layer to ensure their preservation. Moreover, it is a useful resource for supporting dissemination and also serves as a teaching resource for student visitors.